An Imitating Wearable Kidney: A Dialectical Replacement For The Cumbersome Dialysis Procedure For Renal Failures - Vishnuvarthanan Govindaraj, Kavipriya Venkatesan,Kiruthish Seethapathy, Sathiyaa Sri Suthanthiram, Saravanan Alagarsamy, Arunprasath Thiyagarajan (International Journal of Advanced Science and Technology, 2020)
The project is determined to endeavor a device, which is a substitute for hemodialysis thatbenefits the renal failure patient to enrich their life span. Renal failure is the ailment where thefunctions of natural kidneys fail to meet up their desires like filtration, absorption, secretion andexcretion. In general the renal failure patients experience dialysis such as hemodialysis andperitoneal dialysis. Hemodialysis is extensively used because of the downsides in the usage ofperitoneal dialysis and hemodialysis procedure is done in hospitals to eradicate wastes fromblood to sustain their lives. Hemodialysis makes inopportune to the patient owing to visiting thehospital twice a week and this could be astounded by using wearable dialysis. Wearable dialysisworks like hemodialysis that is portable, easy to handle and doesn’t involve any support from thestaffs. This contemporary technology which makes possible the progress of wearable dialysis isintended in such a way to give efficacy results.